Sales Promotion Produk Smartphone di Instagram - Erhan Alviansyah Novendra; Anne Ratnasari (Bandung Conference Series: Communication Management, 2024)
Abstract. Currently, technological advances have a big influence on the development of the times. This development has had a huge impact on the business world. Gebcell is a smartphone shop that uses Instagram social media to carry out its promotions. The research aims to determine the form of sales promotion, message style, and tips and tricks content used by Gebcell on Instagram social media. The research method used in this research is a qualitative research method with a constructivist paradigm and a case study approach. By using this research method, the author wants to know more about the sales promotion of the Gebcell store on the social media Instagram @gebcell. Data collection techniques were carried out using interviews, observation and documentation. The informants taken in this research were the CEO of Gebcell as well as the smartphone sales business owner, marketing manager, admin, and content creator of Gebcell on Instagram @gebcell. The research results show the forms of sales promotion used by Gebcell in marketing smartphone products through social media Instagram accounts, the message style used by Gebcell in marketing smartphone products through Instagram media and information on tips & tricks which are unique in marketing smartphone products on Gebcell's Instagram. Abstrak. Pada saat ini, kemajuan teknologi sangat berpengaruh pada perkembangan zaman. Perkembangan tersebut sangat berpengaruh dalam dunia usaha. Gebcell adalah toko smartphone yang menggunakan media sosial Instagram untuk melakukan promosinya. Penelitian memiliki tujuan untuk mengetahui bentuk sales promotion, gaya pesan, dan konten tips and tricks yang digunakan oleh Gebcell di Media sosial Instagram. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan paradigma konstruktivis dan pendekatan studi kasus. Dengan menggunakan metode penelitian ini, penulis ingin mengetahui lebih dalam tentang sales promotion toko Gebcell pada media sosial Instagram @gebcell. Teknik pengumpulan data yang dilakukan menggunakan wawancara, observasi, dan dokumentasi. Informan yang di ambil dalam penelitian ini adalah CEO Gebcell sekaligus pemilik usaha penjualan smartphone, manajer marketing, admin, dan content creator Gebcell selaku pembuat konten pada Instagram @gebcell. Hasil penelitian menunjukkan bentuk-bentuk Sales promotion yang digunakan oleh Gebcell dalam memasarkan produk smartphone melalui media sosial akun Instagram, Gaya pesan yang digunakan oleh Gebcell dalam memasarkan produk smartphone melalui media Instagram dan informasi tips&tricks yangmenjadi keunikan dalam memasarkan produk smartphone pada Instagram Gebcell.